Validating endpoints for therapeutic trials in fecal incontinence. Issue 8 (6th March 2016) - Noelting, J.; Zinsmeister, A. R.; Bharucha, A. E.
Abstract: Background: A 50% or greater reduction in the frequency of fecal incontinence (FI) recorded with daily bowel diaries is the primary endpoint in clinical trials of FI. Whether this difference is clinically important is unknown. The relationship between FI symptoms recorded with daily and weekly instruments is unknown. The contribution of psychological factors to quality of life (QOL) in FI is unclear. Methods: Fecal incontinence severity was assessed with daily bowel diaries and periodic questionnaires (fecal incontinence severity score [FISS], FIQOL, 36‐Item Short Form Health Survey [SF‐36], and hospital anxiety and depression scales) for 4 weeks before and during double‐blind randomization to placebo or clonidine in 44 women with FI. The reduction in FI frequency was compared to the minimal clinically important difference (MCID) computed from the FISS. Endpoints of FI were compared between daily and weekly diaries. Key Results: The FISS exceeded the MCID in 75% and 83% of patients in whom the FI frequency declined by 50–74% and ≥75% respectively. Parameters of FI measured with daily and weekly instruments were significantly correlated. The daily parameters explained 71% of the inter‐patient variation in the FISS. The SF‐36 health scores, rather than the FISS rating, explained a majority of the inter‐subject variation in FIQOL. Conclusions & Inferences: Most patients who report a ≥50% reduction in FI frequency experience a clinically important improvement. Weekly questionnaires accurately assess the severity of FI. Self‐reported physical and mental health explained a greater proportion of the variance in FIQOL than FI symptom severity. Abstract : This study suggests that a 50% reduction in the frequency of fecal incontinence (FI) is clinically meaningful. Daily and weekly instruments are correlated for assessing symptoms of FI.